2006
DOI: 10.1080/09540100600565895
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bifidobacterial cytoplasm peptide and protein fractions on mouse lymphocyte proliferation and cytokine production

Abstract: The ability of peptides and proteins from Bifidobacterium lactis Bb12 cytoplasm to elicit immune responses was measured in terms of murine splenocyte proliferation and cytokine secretion. Peptides and proteins from B. lactis Bb12 cytoplasm were separated into acidic and basic fractions by liquid-phase electrofocalization based on isoelectric pH. Both fractions were further fractionated by RP-HPLC based on hydrophobicity. Major peaks (of low hydrophobicity) selected in each fraction were found by mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
5
0
2
Order By: Relevance
“…Amrouche et al (2006a) showed that the SI of lymphocyte induced by cytoplasmic content and cell wall of Bifidobacterium lactis Bb12 at the concentrations of 200 lg protein ml -1 were significantly lower (P \ 0.05) than those at the concentrations of 20 and 40 lg protein ml -1 . Ghadimi et al (2008) thought that the optimum immunomodulating effect by live bacteria and DNA of several probiotic bacteria at bacteria/ PBMCs ratio of 10:1 and 75 lg DNA ml -1 was due to the average number of pathogen-associated molecular patterns receptors, such as Toll like receptors (TLRs) and nucleotide binding oligomerization domain (NODs) on the PBMCs.…”
Section: Pbmcs Proliferation Induced By Lactobacilli and Their Cell Cmentioning
confidence: 91%
See 1 more Smart Citation
“…Amrouche et al (2006a) showed that the SI of lymphocyte induced by cytoplasmic content and cell wall of Bifidobacterium lactis Bb12 at the concentrations of 200 lg protein ml -1 were significantly lower (P \ 0.05) than those at the concentrations of 20 and 40 lg protein ml -1 . Ghadimi et al (2008) thought that the optimum immunomodulating effect by live bacteria and DNA of several probiotic bacteria at bacteria/ PBMCs ratio of 10:1 and 75 lg DNA ml -1 was due to the average number of pathogen-associated molecular patterns receptors, such as Toll like receptors (TLRs) and nucleotide binding oligomerization domain (NODs) on the PBMCs.…”
Section: Pbmcs Proliferation Induced By Lactobacilli and Their Cell Cmentioning
confidence: 91%
“…The cell wall of the lactobacilli were prepared according to the method described by Heumann et al (1994) and Amrouche et al (2006a). Briefly, after 18 h incubation the bacterial cells from 50 ml of lactobacilli cultures were harvested by centrifugation (5,000g, 10 min, 4°C) and washed twice with PBS (pH 7.2).…”
Section: Preparation Of Cell Wall Of Bacterial Strainsmentioning
confidence: 99%
“…The fraction exhibiting the highest proliferative activity from gel filtration chromatography was further purified according to the previous methods (Amrouche, Boutin, & Fliss, 2006;Cheng, Wang, Hsu, & Hwang, 2015). This fraction was purified using RP-HPLC on a SunFire TM C18 column (5 µm, 4.6 mm × 250 mm, Waters, USA).…”
Section: Rp-hplc Purificationmentioning
confidence: 99%
“…Вивчення впливу різних фракцій цитоплазматичних пептидів та білків B. lactis виявило стимулювальний вплив похідних на про-ліферативну активність спленоцитів у разі застосування Alamar Blue ® як маркера клітинної проліферації (Amrouche et al, 2006). Вираженість стимулювального впливу залежала від фракціїi та мала концентраційнозалежний характер.…”
Section: обговоренняunclassified
“…Порівнюючи отримані у цій статті дані та результати досліджень впливу дериватів лакто-та біфідобактерій на метаболічну активність спленоцитів миші із застосуванням Alamar Blue ® -тесту інших авторів (Amrouche et al, 2006;Bauer et al, 2010;Kang et al, 2016), ми дійшли висновку: ефект похідних пробіотичних бактерій залежить від штаму, умов культивування пробіотика, способу отримання та біохімічного складу кінцевого продукту. Різноспрямований характер впливу дериватумісних продуктів на спленоцити у нашому (пригнічення) та вищезазначених дослідженнях (стимуляція) можна пояснити, спираючись на фундаментальну біомедичну парадигму гормезису, згідно з якою малі дози стимулюють, а великіінгібують біологічні показники (Shafran et al, 2010).…”
Section: обговоренняunclassified